2019
DOI: 10.26879/930
|View full text |Cite
|
Sign up to set email alerts
|

Alternating stripmining and sequestration in deep-sea sediments: The trace fossil Polykampton–an ecologic and ichnotaxonomic evaluation

Abstract: Polykampton Ooster, 1869, comprises deep-sea trace fossils composed of a horizontal median cylindrical tunnel and lateral spreite lobes that alternate on either side of the tunnel and are slightly inclined to bedding. The lobes in P. alpinum Ooster, 1869, are closely spaced and partly shingled. In P. guberanum isp. nov. they are asymmetric and widely spaced. In both ichnospecies, the lobes are generally below the median tunnel. In P. multiflabellatum isp. nov., the lobes extend from outer bents of the median t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The trace fossil Polykampton Ooster, 1869, typified by P. alpinum Ooster, 1869 from the Paleogene flysch deposits of Switzerland, was almost forgotten for more than a century and treated as a monospecific ichnogenus (Häntzschel, 1975;Seilacher, 2007). Discoveries of four new ichnospecies of Polykampton from Cretaceous-Oligocene flysch deposits (Wetzel and Uchman, 1997;Uchman and Rattazzi, 2018;Uchman et al, 2019Uchman et al, , 2020 showed that this ichnogenus is more diverse and widespread than previously thought. In this paper, a sixth named ichnospecies of Polykampton is described and interpreted.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…The trace fossil Polykampton Ooster, 1869, typified by P. alpinum Ooster, 1869 from the Paleogene flysch deposits of Switzerland, was almost forgotten for more than a century and treated as a monospecific ichnogenus (Häntzschel, 1975;Seilacher, 2007). Discoveries of four new ichnospecies of Polykampton from Cretaceous-Oligocene flysch deposits (Wetzel and Uchman, 1997;Uchman and Rattazzi, 2018;Uchman et al, 2019Uchman et al, , 2020 showed that this ichnogenus is more diverse and widespread than previously thought. In this paper, a sixth named ichnospecies of Polykampton is described and interpreted.…”
Section: Introductionmentioning
confidence: 84%
“…However, there are no traces of reworking of the lobes. This is a repetitive problem in all ichnospecies of Polykampton, which can be explained by the possibility that the food can be obtained by ingestion without reworking by means of exoenzymes produced by bacteria, as proposed for the other ichnospecies of Polykampton (Uchman and Rattazzi, 2018;Uchman et al, 2019Uchman et al, , 2020. Labile organic matter can be released from particulate organic matter by exoenzymes (e.g., Aller and Cochran, 2019) and leached into the main tunnel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polykampton consists of a central, mainly horizontal, slightly winding tunnel having rather narrow-spaced, petal-like lobes filled with fine-grained, organic-rich material on either side (Uchman et al, 2019). The studied specimens occur within a few tens of meters thick interval in Palaeogene muddy turbidites in the Lesser Caucasus (Georgia).…”
Section: Influence Of Variable Benthic Food Availability In Flysch On...mentioning
confidence: 99%